Implementasi Lesson Study Dalam Pembelajaran Pendidikan Agama Katolik - Yonas Atjas (Institut Agama Kristen Negeri Tarutung, 2022)
Abstract:The purpose of this research to describe the concepts and characteristics of Lesson Study and to implement the Lesson Study in learning Catholic Religious Education. Lesson Study is collaborative and sustainable activities by the principles of collegiality, mutual learning and learning community. The method of this research is descriptive-qualitative method. The results showed that a model of teacher professional development by teaching and learning in a collaborative and sustainable manner based on the principles of collegiality and mutual learning and building a learning community. The implementation of Lesson Study in the learning of Catholic Religious Education follows the stages: planning, observing and reflecting. The conclusion is the principal should improve the professionalism of teachers by implementing Lesson Study in schools so that it is be a school culture.Keywords: lesson study, catholic religious education, collaborativeAbstrak:Tujuan penelitian ini adalah menganalisis konsep dan karakteristik Lesson Study serta mengimplementasikan tahap-tahap Lesson Study dalam pembelajaran Pendidikan Agama Katolik. Lesson Study merupakan aktivitas-aktivitas kolaboratif dan berkelanjutan melalui prinsip-prinsip kolegalitas, mutual learning dan learning community. Metode yang digunakan dalam penelitian ini adalah metode deskriptif-kualitatif. Hasil penelitian menunjukan bahwa suatu model pembinaan profesi guru melalui belajar mengajar (pengkajian pembelajaran) secara kolaboratif dan berkelanjutan berlandaskan prinsip-prinsip kolegalitas dan mutual learning dan membangun learning community. Implementasi Lesson Study dalam pembelajaran Pendidikan Agama Katolik mengikuti tahap-tahap yakni merencanakan (plan), mengamati (observe) dan melakukan refleksi (reflect) terhadap pembelajaran (lesson). Kesimpulan yang diberikan adalah kepala sekolah hendaknya meningkatkan profesionalitas guru dengan menerapkan Lesson Study di sekolah sehingga menjadi budaya sekolah. Kata Kunci: lesson study, pendidikan agama katolik, kolaboratif